Antiviral immune responses in human reproductive tract: Pathogenic mechanisms and therapeutic implications - Kim-Ling Chin; Nurhafiza Zainal (Asian Pacific Journal of Tropical Medicine)
Viral reproductive tract infections (VRTIs) are a significant global health concern with severe consequences, including infertility, chronic pelvic pain, and increased risk of HIV transmission. Complex interplay between pathogens and the host immune system plays a critical role in the pathogenesis and treatment of VRTIs. This review aims to provide a comprehensive overview of the multifaceted roles of the immune system in both contributing to and combating VRTIs. The review will also address the consequent perturbations in immune homeostasis and the implications for disease manifestation and progression. The interrelation between systemic immunity and local immune responses is discussed, providing insights into the challenges and breakthroughs in managing these infections. By providing a comprehensive overview of the mechanisms, implications, and therapeutic strategies associated with viral reproductive tract infections and immune dysfunction, this review also informs future research and clinical practice in this important area of reproductive health.